ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL CERITA DENGAN FONG’S SCHEMATIC MODEL FOR ERROR ANALYSIS PADA MATERI SISTEM PERSAMAAN LINEAR TIGA VARIABEL - Hilda Sara; Elin Marlina; Dhea Dwi Agustin; Jaka Haerul (Jurnal Edukasi dan Sains Matematika (JES-MAT), 2020)
This study aims to describe the types of errors and the factors that cause students to mistake in solving word problems with Fong's Schematic Model for Error Analysis on the material system of three-variable linear equations. This research uses a qualitative research approach. The study participants consisted of 3 high school grade X students in one of the high school in Kuningan. Subjects in the study were selected using a purposive sampling technique. Research data collection using the method of documentation, tests, and interviews. Checking the validity of the data using triangulation techniques, by collecting different data to get data from the same source through tests, interviews and documentation. Based on the results of data analysis, it can be concluded that the types of students' mistakes in solving word problems are operational errors and mathematical themes. Factors causing student errors include: the rush to immediately solve a problem, the lack of accuracy, the habit of working on the problem, forgetting, lack of understanding of the problem, and lack of understanding of the material.